ANALISIS PENDAPATAN DAN PENERIMAAN INDUSTRI GULA MERAH TEBU DI DESA LINDUNG JAYA KECAMATAN KAYU ARO KABUPATEN KERINCI - Endy Effran (Jurnal Bisnis Tani, 2022)
AbstractThis study aims to: (1) describe the general description of the brown sugar cane agro- industry business in the Protected Jaya Village, Kayu Aro District, Kerinci Regency. (2) Knowing the income and R/C ratio of brown sugar cane agroindustry in Lindung Jaya Village, Kayu Aro District in Kerinci Regency. The data collection in this thesis was carried out by observation and interview methods. Interviews were conducted with 5 agro- industries located in the Protected Jaya Village, Kayu Aro District in Kerinci Regency. The analytical method used is descriptive analysis, business analysis and R/C ratio. Based on the results of the study, there were 5 agro-industry that developed in the Lindung Jaya Village, Kayu Aro District, Kerinci Regency, (1) Lindung Jaya Village, Kayu Aro District, Kerinci Regency, which is a home industry center for brown sugar cane which is consumed as a natural sweetener in food in the form of plots. and made without preservatives. (2) The average income received by the brown sugar cane agroindustry is Rp. 5,067,013,- per month. The average fixed cost incurred is Rp. 225,137, - which consists of mill rental costs and equipment depreciation, and the average variable costs incurred per month are Rp. 1,504,950. The R/C value obtained by each brown sugar agroindustry >1 means that this brown sugar cane agroindustry is profitable and feasible to continue.Keywords: Sugar Cane, Agroindustry, Revenue